Vesicle trafficking pathways that direct cell migration in 3D matrices and in vivo. (10th September 2018) - Wilson, Beverley J.; Allen, Jennifer L.; Caswell, Patrick T.
Abstract : Cell migration is a vital process in development and disease, and while the mechanisms that control motility are relatively well understood on two‐dimensional surfaces, the control of cell migration in three dimensions (3D) and in vivo has only recently begun to be understood. Vesicle trafficking pathways have emerged as a key regulatory element in migration and invasion, with the endocytosis and recycling of cell surface cargos, including growth factor and chemokine receptors, adhesion receptors and membrane‐associated proteases, being of major importance. We highlight recent advances in our understanding of how endocytic trafficking controls the availability and local activity of these cargoes to influence the movement of cells in 3D matrix and in developing organisms. In particular, we discuss how endocytic trafficking of different receptor classes spatially restricts signals and activity, usually to the leading edge of invasive cells. Abstract : Vesicle trafficking pathways control the delivery of cargos to and from the plasma membrane, and thus regulate their availability. Here, we review the function of endocytic trafficking in mediating the cell surface localization and local activity, through spatial restriction, of key cargoes that drive cell migration and invasion in three‐dimensional matrix and in vivo.